An exact algorithm for the minimum squared load assignment problem - Karsu, Özlem; Azizoglu, Meral (Computers & operations research, 2019)
•We study the minimum squared load assignment problem.•We formulate the problem as a mixed integer linear programming model.•We present a branch and bound algorithm for its solution.•Our computational experiments show the satisfactory behavior of the algorithm. In this study, we consider an assignment problem with the objective to minimize the sum of squared loads over all agents. We provide mixed integer nonlinear and linear programming formulations of the problem and present a branch and bound algorithm for their solution. The results of our computational experiment have shown the satisfactory behavior of our branch and bound algorithm.